The Development of Coach – Athlete Relationship Questionnaire: CART-Q - Sritapunya, Wanicha; Wongjaturapat, Naruepon; Tongkhumbunjong, Seksan; ฺBoonweesabutr Suebsai (Academic Journal of Thailand National Sports University, 2022)
The purpose of this study was to development of Coach-Athlete Relationship Questionnaire (CART-O). Participants were 600 students in sport school (junior high school and senior high school) from 12-18 to years of age. The CART-Q was developed by Jowett, & Ntoumanie (2004) and translated into Thai language. This study on process of translation. Result indicated that the Coach-Athlete Relationship Questionnaire: Closeness, Commitment, Complementarity (X?/df = 1.47, GFI = 0.95, AGFI = 0.88, NNFL = 0.98, CFL = 0.99, RMSEA = 0.056), alpha reliability and composite reliability scale were 0.87. Conclude that the questionnaire is acceptable.